The potential of abandoned heritage buildings as tourism attraction: a case study in Papan, Perak / Nurul Asyikin Khairudin ... [et al.] - Khairudin, Nurul Asyikin; Ramele Ramli, Rohaslinda; Abu Bakar, Abdullah Anas; Retna Hidayah (UiTM Press, 2024)
This research explores the potential of abandoned heritage buildings as a tourism attraction, focusing on abandoned heritage buildings in Papan, Perak. These buildings, once significant in their era, now stand dilapidated and abandoned, evoking both aesthetic allure and safety concerns. Despite the inherent dangers, enthusiasts of dark tourism are drawn to these neglected structures. The study aims to investigate the viability of leveraging Papan's abandoned heritage buildings for tourism purposes. Key objectives include identifying the heritage significance of these abandoned buildings, assessing tourist expectations and satisfaction regarding Papan's abandoned buildings, and proposing strategies for their development as tourist attractions. Employing a quantitative method approach, the author distributed questionnaires to tourists who have and have not visited Papan. Findings indicate significant potential for Papan as a tourist destination, as evidenced by positive responses from respondents. However, dissatisfaction with tourism facilities and safety highlights areas for improvement. Overall, the research underscores the allure of abandoned heritage buildings and provides valuable insights for enhancing Papan's appeal as a heritage tourism destination.